Penerapan Model Pembelajaran Teams Games Tournament Untuk Meningkatkan Keaktifan Siswa Pada Mata Pelajaran Pendidikan Pancasila - Ludia Alfafa Faza (Universitas Negeri Semarang, 2026)
Pancasila Education is one of the subjects that has a strategic role in shaping the character and identity of the nation. However, despite its strategic position in the national curriculum, the implementation of Pancasila Education learning in the field still faces various challenges. One of the main challenges is the learning approach which is still dominated by the lecture method, is textual, lacks innovation, and lacks active participation of students. Based on this, there needs to be innovation in learning models. This study aims to determine the implementation of the team games tournament learning model and its effectiveness in increasing student activity. This study is a type of classroom action research with a qualitative approach. Data collection techniques use observation, interviews, and documentation. The results of the study showed that the implementation of the team games tournament learning model consists of 3 stages, namely opening, core, and closing. At this stage, there are 4 phases, namely presentation of material, organizing teams, implementing tournaments, and team recognition. The Team Games Tournament (TGT) learning method is effective in increasing student activity in the Pancasila education subject of international relations material.